Development of chitosan/heparin nanoparticle-encapsulated cytolethal distending toxin for gastric cancer therapy. (June 2014) - Lai, Cheng-Kuo; Lu, Yu-Luen; Hsieh, Jer-Tsong; Tsai, Shih-Chang; Feng, Chun-Lung; Tsai, Yuh-Shyan; Tsai, Pei-Ching; Su, Hong-Lin; Lin, Yu-Hsin; Lai, Chih-Ho
Aim: The aim of this work was to develop pH-responsive nanoparticles encapsulating CdtB and to demonstrate that these particles represent a potential therapeutic agent for gastric cancer.Materials & methods: Chitosan/heparin nanoparticle-encapsulated CdtB was prepared and the delivery efficiency was monitored by confocal laser scanning microscopy. The molecular basis of the nanoparticle-encapsulated CdtB-mediated p53 activation pathway was explored by immunoblot analysis. Antitumoral activities were investigated by analyzing the cell cycle and apoptosis.Results: Chitosan/heparin nanoparticle-encapsulated CdtB preferentially inhibited the proliferation of cells derived from gastric cancer, but not in primary gastric epithelial cells. Treatment of cells with nanoparticle-encapsulated CdtB enhanced cell-cycle arrest at G2/M, followed by apoptosis. Moreover, our data showed that the mechanism for nanoparticle-encapsulated CdtB-induced cell death was mediated by ATM-dependent DNA damage checkpoint responses.Conclusion: These findings indicate that chitosan/heparin nanoparticle-encapsulated CdtB could represent a new CdtB delivery strategy for the treatment of gastric cancer. Original submitted 8 May 2012; Revised submitted 5 February 2013